RE-EVALUATING ACCOUNTING CONSERVATISM AND ITS IMPACT ON TAX EVASION STRATEGIES: EVIDENCE FROM DISCLOSURE AND TRANSPARENCY (World Economics and Finance Bulletin, 2026)
This research study aims to test the relation between accounting conservatism and tax evasion among Iraqi non-financial firms and the moderating effect of transparency and information disclosure.